2023
DOI: 10.3390/ijms241310898
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Developmental Effects of Bisphenol F Exposure in Chinese Medaka (Oryzias sinensis)

Abstract: Bisphenol F (BPF) has been used in the syntheses of polymers, which are widely used in coatings, varnishes, adhesives, and other plastics. During the past decades, BPF contamination in the aquatic environment has dramatically increased due to its release from manmade products. Concerns have driven much attention to whether it may adversely impact aquatic lives or human beings. The present study performed an acute toxic exposure experiment and a 15 d developmental exposure of BPF at environmental concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 56 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…The 96 h acute exposure showed that BPS was not lethal up to 1000 mg/L for Chinese medaka embryos. In a previous study, for a 96 h acute exposure, the LC50 of bisphenol F (BPF) was 87.90 mg/L for Chinese medaka embryos [ 48 ], suggesting that BPS is less toxic than BPF. In cell models, researchers found that the LC50 of BPS on fish primary macrophages was 39.1 mg/L and 29.7 mg/L after a 6 h or 12 h exposure, respectively [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The 96 h acute exposure showed that BPS was not lethal up to 1000 mg/L for Chinese medaka embryos. In a previous study, for a 96 h acute exposure, the LC50 of bisphenol F (BPF) was 87.90 mg/L for Chinese medaka embryos [ 48 ], suggesting that BPS is less toxic than BPF. In cell models, researchers found that the LC50 of BPS on fish primary macrophages was 39.1 mg/L and 29.7 mg/L after a 6 h or 12 h exposure, respectively [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese medaka were obtained from a local aquarium store and cultured in the laboratory as previously described [ 48 ]. All applicable institutional and/or national guidelines for the care and use of animals were followed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations